Learning Flipped Model as Implementation of Inqury Revised Community to Enhance Economics Students' Learning Achievement - Fransisca Desiana Pranatasari; Januari Ayu Fridayani (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2020)
Progress in technology impacts the educational sector, which allows teachers to build interactive learning programs. The goal of this study is to investigate the use of the flipped learning model to improve student learning outcomes as the implementation of the revised community of inquiry (RCOI). The research was carried out on students who took the course in Organizational Management, Management Study Program, Economics Faculty, Sanata Dharma University. A purposeful sampling method was used for the sampling technique, data mining used questionnaires for 163 respondents and classroom surveys. Three factors are included in the aspects examined, specifically the characteristics of the learning program, implementation and the outcomes obtained. The data analysis was using factor analysis. The findings showed that learners thought the stimuli using the flipped learning model made learning simpler and more autonomous for them and this RCOI measure provided its advantages in influencing the progress of their learning outcomes. Keywords: Model Flipped Learning, Revised Community of Inquiry (RCOI), Students’ Learning Outcomes